Press Release from the California Democratic Delegation - Dick Kline:::::: (1968)
A press release from Assembly Speaker Jesse M. Unruh announces the full list of delegates comprising California's 174-vote delegation to the Democratic National Convention in Chicago. The delegation includes 25 newly appointed members filling vacancies caused by recent resignations. Notable new delegates include leaders and prominent figures such as Martin Stone, Gerald Hill, Charles Warren, Pierre Salinger, Frank Mankiewicz, Carmen Warschaw, and Jane Tolmach. The release also lists the delegates who resigned and notes that Democratic National Committeeman Eugene Wyman and Committeewoman Ann Alanson serve as ex officio members. A complete roster of delegates from across California is provided, with one remaining vacancy in San Bernardino County to be filled soon.